A Identification of fungal diseases of Swertia chirayita of Sankhuwasabha district - Dhakal, Manisha; Jha, Sanjay Kumar (Journal of Natural History Museum, 2022)
Swertia chirayita is one of the important medicinal and highly traded plant for commercial purpose. However, its production has significantly declined in recent days due to incidence of various diseases. Unfortunately, the knowledge on disease and its causative agent is insufficient. Therefore, the present study focuses on incidence and severity of disease and identification of causative agents. The disease incidence of plant of study cultivated field of Sankhuwasabha district was 53.20% and the disease severity was 23.87%. Leaf spot disease caused by Alternaria alternata, Botrytis cinera and Bipolaris sorokiniana, leaf blight caused by Colletotrichum gloeosporioides and Fusarium wilt by Fusarium oxysporum and rot disease caused by Trichoderma harzianium were identified in Swertia chirayita.